Effectiveness of Mindfulness Based Treatment for Female Victims of Violence - Latif, Abeera; Safdar, Faiza; Javed, Muhammad Latif (Pakistan Journal of Humanities and Social Sciences, 2025)
The present study was designed to examine the effectiveness of mindfulness-based stress reduction for female victims of violence. It was hypothesized that mindfulness-based stress reduction (MBSR) will increase resilience and secondary control engagement coping and decrease primary control engagement coping and among female victims of violence. Quantitative data was collected from a sample (N=20) of women who have experienced physical, emotional, and economic violence and were recruited from governmental and non-governmental organizations located in Lahore, Pakistan. An experimental research design with a non-probability purposive sampling strategy was used. Posttraumatic Diagnostic Scale (Foa et al., 2016) was utilized as a screening tool and Brief Resilience Scale (Smith et al., 2008) and Response to Stress Questionnaire (Connor-Smith et al., 2000) was used as assessment measures. Statistical analyses such as reliability analysis, descriptive analysis, Mann-Whitney U, and Wilcoxon sign rank tests were performed. The results of the present study revealed that mindfulness-based stress reduction (MBSR) significantly increased resilience and secondary engagement coping in participants. The implications of the present study highlight the need to adapt MBSR for victims of sexual violence and for individual therapeutic sessions.